Answer:
2 1/4 or 2.25
Step-by-step explanation:
2*3= 6
3/4*3= 2 1/4
1/3
Reduces los números usando el máximo común divisor= 2
Step-by-step explanation:
Given ![g'(x) = g^{-2}, x> 0\ g(1) = 0 \ and \ g(2) = 0](https://tex.z-dn.net/?f=g%27%28x%29%20%3D%20g%5E%7B-2%7D%2C%20x%3E%200%5C%20g%281%29%20%3D%200%20%5C%20and%20%5C%20g%282%29%20%3D%200)
To get g(x), we will have to integrate g'(x)
![g(x) = \int\limits {x^{-2}} \, dx\\ g(x) = \frac{x^{-2+1}}{-2+1} + C\\ g(x) = -x^{-1} + C\\g(x) = -x^{-1} + C\\](https://tex.z-dn.net/?f=g%28x%29%20%20%3D%20%5Cint%5Climits%20%7Bx%5E%7B-2%7D%7D%20%5C%2C%20dx%5C%5C%20g%28x%29%20%20%3D%20%5Cfrac%7Bx%5E%7B-2%2B1%7D%7D%7B-2%2B1%7D%20%2B%20C%5C%5C%20g%28x%29%20%3D%20-x%5E%7B-1%7D%20%2B%20C%5C%5Cg%28x%29%20%3D%20-x%5E%7B-1%7D%20%2B%20C%5C%5C)
If g(1) = 0, this means at x = 1, g(x) = 0
0 = -1⁻¹ + C
C= 1
Substitute C = 1 into the function
g(x) = -x⁻¹ + 1
If g(2) = 0, this means at x = 2, g(x) = 0
0 = -2⁻¹ + C
C= 2⁻¹
C = 1/2
Substitute C = 2 into the function
g(x) = -x⁻¹ + 1/2